Medición con ítem único del agotamiento emocional académico en estudiantes universitarios peruanos: evidencias de validez y confiabilidad - Dominguez-Lara, Sergio Alexis (2019)
Abstract: The aim of this study was to obtain evidence of validity and reliability of the Single Item Academic Emotional Exhaustion (IUAEA). Was assessed a total sample of 227 college students (155 women) between 17 and 56 years (M=23.52, SD=5.972), and a subsample of 116 subjects (79 women) for the temporal stability study. In addition to the IUAEA, it was used the Escala de Cansancio Emocional (ECE) as external criterion. Evidence of validity were analyzed with structural equation modeling through the whole modeling of IUAEA with items of ECE; correlations between IUAEA and ECE; and a comparative analysis of their relationship with sociodemographic aspects (sex, work activity). Reliability analysis performed shows satisfactory results in terms of internal consistency and temporal stability of IUAEA. The results are consistent with other studies on the validity of the measure single item. The results and their implications are discussed.